Parametric study of multiplanar tubular DX- and XT-joints - Lee, Wooi Min. (2009)
Steel multiplanar tubular joints are an intrinsic feature of offshore steel structures. However, current design codes used for the prediction of fatigue strength of uniplanar and multiplanar joints are based on the numerical and experimental results of simple uniplanar joints. To date, there are still very few numerical and experimental results on multiplanar joints that are available for verification and codification purposes.